Optimization of microwave irradiation time for KOH-activated carbon from oil palm fronds - Rahmat Zikri; Ayu Sapitri; Yolanda Rati (Acta Chimica Asiana, 2025)
Activated carbon is a widely applied adsorbent material in wastewater treatment, whose physical and chemical properties are strongly influenced by the activation method employed. Microwave irradiation–based physical activation has emerged as an attractive alternative, offering shorter processing times and lower energy consumption compared to conventional heating methods. This study aims to evaluate the effect of varying microwave irradiation times on the characteristics of activated carbon derived from oil palm fronds (OPF) waste. The synthesis process began with carbonization at 600 °C for 60 minutes to produce OPF char, followed by chemical activation using KOH with a char-to-KOH mass ratio of 1:1 (g/g) in 100 mL of demineralized water, and subsequently physical activation using a microwave at 200 W for 5 minutes (A5D200), 10 minutes (A10D200), and 15 minutes (A15D200). Characterization was conducted in accordance with SNI 06-3730-1995 standards (moisture content, ash content, and iodine adsorption capacity), as well as physicochemical analyses including crystallinity, surface area, functional groups, morphology, and elemental composition. The results demonstrated that all samples met the SNI requirements, with the highest iodine adsorption capacity (828.69 mg/g) and the largest surface area (824.26 m²/g) obtained at A10D200. XRD analysis revealed the dominance of amorphous structures with an increasing Lc/La ratio as the irradiation time increased, while SEM images showed relatively small and uniformly distributed pores. FTIR spectra confirmed the presence of O–H, C=O, C=C, C–H, and C–O functional groups. In conclusion, a 10-minute irradiation time produced activated carbon with an optimal balance between pore structure, surface area, and adsorption capacity